2004
DOI: 10.1001/jama.291.11.1342
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Prognosis of "Masked Hypertension" Detected by Blood Pressure Self-measurement in Elderly Treated Hypertensive Patients

Abstract: HE REFERENCE METHOD FOR blood pressure (BP) measurement during clinical consultations is the auscultatory method with a mercury sphygmomanometer. This method has been used to demonstrate the relationship between BP and cardiovascular risk. A meta-analysis of individual data from almost 1 million adults participating in 61 prospective studies precisely established the prognostic value of this method of measurement: for each increase of 10 mm Hg in systolic BP (SBP) or 5 mm Hg in diastolic BP (DBP), the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
416
6
15

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 751 publications
(481 citation statements)
references
References 28 publications
33
416
6
15
Order By: Relevance
“…17 The measurement of BP in a clinical setting tends to be a stressor itself, and can falsely increase BP and BP reactivity through what is recognized as the white coat effect. 18 Our observations provide additional support for the clinical usefulness of HBPM, 19 as compared with that of conventional clinical BP readings, [9][10][11] by demonstrating that HBPM data are likely to show good reproducibility, not only for sitting BP levels but also with respect to orthostatic BP changes.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…17 The measurement of BP in a clinical setting tends to be a stressor itself, and can falsely increase BP and BP reactivity through what is recognized as the white coat effect. 18 Our observations provide additional support for the clinical usefulness of HBPM, 19 as compared with that of conventional clinical BP readings, [9][10][11] by demonstrating that HBPM data are likely to show good reproducibility, not only for sitting BP levels but also with respect to orthostatic BP changes.…”
Section: Discussionmentioning
confidence: 53%
“…3,[5][6][7][8] Home BP monitoring (HBPM) has been recently recommended as a convenient and reproducible method of BP measurement in hypertension management, with a better prognostic value than clinical BP measurements. [9][10][11] However, no data are available on the reproducibility of orthostatic BP changes when assessed by means of HBPM, which we previously showed to be more closely associated with increased albuminuria than when patients were assessed by clinical BP. 4 Hyperactivation of the sympathetic nervous system has been suggested as one of the mechanisms of OHT, in line with our previous finding that BP increase during head-up tilt in OHT subjects was blunted by alpha-adrenergic blockade.…”
Section: Introductionmentioning
confidence: 99%
“…41 Both ABPM and SBPM can identify true hypertension, white coat hypertension and masked hypertension (normal office BP and elevated out of office BP). White coat and masked hypertension are common, each affecting 10-15% of the general population, with the latter associated with a doubling of cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…25 Furthermore, prospective studies have revealed that a high ambulatory or home BP is a powerful predictor for cardiovascular morbidity and mortality in the general population and treated hypertensive patients even when their office BP is normal or well controlled. 10,11,[26][27][28] As for the association between LV geometry and cardiovascular prognosis, it was reported that hypertensive patients with concentric hypertrophy among four LV geometric patterns had the highest incidence of cardiovascular events and death. 13 Taken together, it is likely that advanced target organ changes including LV concentric hypertrophy in patients with masked hypertension or reverse whitecoat condition are linked to poor cardiovascular prognosis in such patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested that an elevated ambulatory or home BP despite a well-controlled office BP is associated with poor cardiovascular prognosis in treated hypertensive patients. 10,11 However, it remains unclear what mechanism is involved in the association of reverse white-coat phenomenon with cardiovascular prognosis.…”
Section: Introductionmentioning
confidence: 99%